A two-stage adaptive allocation design for survival outcome with informative censoring. (2nd October 2018) - Bhattacharya, Rahul; Shome, Madhumita
ABSTRACT: An adaptive two-stage allocation design is developed for survival responses subject to independent informative censoring. The asymptotic p value of a score test related to a hypothesis of treatment effectiveness is used to set the assignment probability of the second stage. Several characteristics of the design and the follow-up inference are studied, both numerically and theoretically, and are compared with those of an existing competitor. Applicability of the proposed design is also illustrated through a real data.